Effect of Acupressure on Nausea in Patients Undergoing Strabismus Surgery - Alireza Nikbakht Nasrabadi; Zahra Alizadeh; Masoomeh Imanipour; Sayed Mostafa Hosseini; Sayed Hossein Sadrosadat; Reza Heshmat (Tehran University of Medical Sciences, 2012)
Background & Aim: Postoperative nausea is a common problem after general anesthesia, especially in ambulatory surgery. In ocular surgeries including strabismus surgery, intraocular pressure increase may lead to eye damage. Drug therapy has various side effects. The purpose of this study was to evaluate acupressure on nausea in patients undergoing strabismus surgery. Methods & Materials: In this double-blinded clinical trial, 60 patients undergoing strabismus surgery were allocated into intervention and control groups. In the intervention group, a sea-band was placed on the P6 point of patients&apos wrists 30 minutes before induction of anesthesia. In the control group, the sea-band was placed in the opposite position of the patients&apos wrists. Data were collected during six hours after surgery in the recovery room. Data were analyzed using Chi square, t-test, and Mann-Whitney tests. Results: There were no differences in demographic and surgical characteristics between the two groups at baseline. The intensity of nausea in the recovery room (P=0.002) and six hours after surgery (P<0.001) were significantly less in the intervention group than the control group. Conclusion: Based on the findings of this study, acupressure decreases post operative nausea. Acupressure is a simple, noninvasive and cost- effective intervention which can be applied by nurses to prevent post operative nausea.